2016
DOI: 10.18805/ijar.8567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milking behavior on circulatory hormones and milk production in lactating Murrah buffaloes

Abstract: The effect of milking temperament on plasma hormones, metabolites, milk yield and composition in lactating Murrah buffaloes was studied. Animals were selected from the institute herd and grouped as docile and nervous buffaloes, based on temperament score before and during milking. Blood sampling times were; before milking (-20 min.), after concentrate intake, after teat massage, during milking and 20 min. post-milking. Plasma prolactin (PRL), growth hormone (GH) and cortisol (CORT) concentrations were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The higher serum cortisol concentration in primiparous animals might be attributed to their more agitated behaviour and less tolerance due to inexperience of routine handling as compared to multiparous animals (Mohammad and Abdel-Rahman 2013). Similarly, Singh et al (2016) reported significantly higher serum cortisol concentration in nervous buffaloes in comparison to docile buffaloes as primiparous animals were more aggressive.…”
Section: Resultsmentioning
confidence: 94%
“…The higher serum cortisol concentration in primiparous animals might be attributed to their more agitated behaviour and less tolerance due to inexperience of routine handling as compared to multiparous animals (Mohammad and Abdel-Rahman 2013). Similarly, Singh et al (2016) reported significantly higher serum cortisol concentration in nervous buffaloes in comparison to docile buffaloes as primiparous animals were more aggressive.…”
Section: Resultsmentioning
confidence: 94%
“…Enhancing PG-based ES with either gonadotropin-releasing hormone (GnRH) or human chorionic gonadotropin (hCG) at the time of AI increases the pregnancy rate from 20% to 37% (Atabay et al, 2020). The use of T A B L E 1 Estrus synchronization protocols and results in swamp and riverine buffaloes using luteolytic and luteotropic agents or in combination with other hormones Chantaraprateep et al, 1981;Chirachaikitti et al, 1982;Chantaraprateep et al, 1983;Capitan et al, 1992;Yuan et al, 2008;Sianturi et al, 2012 PG Virakal et al, 1988 Norgestomet + PMSG 45.5 39.13 Virakal et al, 1988 Riverine PG single dose 75.0-100.0 41.5-80.0 Pant & Singh, 1991;Khattab et al, 1996;Ribeiro et al, 1998;Brito et al, 2002 PG double dose 11-12 days apart 25.0-95.0 22.8-83.0 Chohan et al, 1993;Diaz et al, 1994;Singh & Dabas, 1998;Misra et al, 2003;Srivastava, 2005. Norgestomet + E2 60.0-100 30.0-70.0 Phadnis et al, 1994;Patel et al, 2003 Norgestomet + eCG 86.0-97.6 44.6-66.7 Luthra et al, 1994;Malik et al, 2011 Norgestomet + PG 100 45.0-66.7 Utage et al, 2010;Chaudhary et al, 2015 Abbreviations: CIDR, controlled internal drug release; E2, estradiol; eCG, equine chorionic gonadotropin; GnRH, gonadotropin releasing hormone; hCG, human chorionic gonadotropin; PG, prostaglandin; PMSG, pregnant mare serum gonadotropin; PRID, progesterone releasing intravaginal device.…”
Section: Estrus Synchronization (Es) In Buffaloesmentioning
confidence: 99%